Yüksek Katılımlı İnsan Kaynakları Uygulamalarının Çalışanların İş Tatmini ve İşten Ayrılma Niyetleri Üzerindeki Etkileri - MERTEL, KÜBRA (My University, 2019)
Introduction With the rapidly changing in business environment, companies give more importance to improving then- capabilities and acknowledge that their competing power and success depend on highly motivated, satisfied, and innovative human resources. Although the use of new technologies, good marketing strategies, and better customer service contribute to firms’ success, human resources are the most important resources for companies to create competitive advantage (Huselid and Becker 1998). This is because technologies, marketing strategy, customer services can be imitated by the competitors while employees’ knowledge, skills and abilities cannot. So, companies must invest in their employees by using effective human resource management practices. Several researchers have so far focused on the relationship between human resource management practices and job satisfaction (Bemardin and Russel 1993; Garcia 2005; Thang and Buyens 2008) and turnover intention (e.g., Huselid 1995). They specifically find that human resource management practices, and particularly high-involvement human resource management practices influence employees’ job satisfaction (Tzafrir 2006; Katou and Budhwar 2007) while they have negative impacts on employees’ turnover intention (Robert et al. 2000). However, previous studies have not investigated the relationship between high involvement human resource management, employees’ job satisfaction, and turnover intention in the same model. Specifically, research to date has not examined the mediating effect of job satisfaction on the relationship between high-involvement human resource management practices and turnover intention. This study aims to fill the aforementioned gaps by examining the relationship between high involvement human resource management and turnover intention in the context of a developing country, namely Turkey. It will also shed light on the mediating role of job satisfaction in the relationship between high involvement human resource management and employees’ turnover intention. In this way, this study intends to contribute the human resource management, job satisfaction, and turnover intention literatures in different ways. It also guides the researchers to conduct similar studies in developing countries such as Turkey which attracts many investors to conduct business in a large market which involves a highly-skilled workforce. Material and Methods In this study, a quantitative research method was used to investigate the relationships between the high- involvement human resource management practices, job satisfaction, and turnover intention. Data were collected from 70 employees working in five different companies operating in the retail industry in Turkey. Collecting data from different companies operating in the same industry helps to generalize the findings of the study for retailing industry in Turkey. In this study, Statistical Package of the Social Sciences {SPPS} version 23 is used to analyze the hypotheses. Results Results revealed that when considered independently, information sharing, empowerment, and fair rewards have significant impacts on turnover intention. On the other hand, when these practices are considered as a whole, only fair rewards and empowerment influence turnover intention. Similarly, when considered individually, each high involvement human resource management practice has an effect on job satisfaction while empowerment is the only practice that influences job satisfaction in the multiple regression model conducted with the three high involvement human resource practices. Consistent with the vast amount of empirical evidence, results indicate a negative relationship between job satisfaction and turnover intention. Mediation analysis reveal that job satisfaction acts as a perfect mediator in the relationship between empowerment and turnover intention. This finding indicates that empowerment increases employees’ job satisfaction which subsequently decreases their turnover intention. Discussion In this research empowerment arises as the only high involvement human resource practice that significantly impacts employees’ job satisfaction and turnover intention. This finding can be also associated with the gender and age levels of the participants. The majority of the respondents in the sample are women (65.9 %) and the mostly represented age group is between 26-45. As the women aged between 26 and 45 may need more empowerment than men may do, empowerment might emerge as the only high involvement human resource practice that significantly impacts outcome variables.
Keywords: High Involvement Human Resource Management Practices; Information Sharing; Empowerment; Fair Rewards; Job Satisfaction; Turnover Intention; Yüksek Katılımlı İnsan Kaynakları Yönetimi Uygulamaları; Bilgi Paylaşımı; Güçlendirme; Adil Ödüller; İş Memnuniyeti; Ciro Niyeti